Peningkatan Kemampuan Membaca Al-Qur’an Mahasiswa Menggunakan Al Qur’an Model Waqfi Wal Ibtidak Melalui Metode Pembelajaran Tahsin - Yusuf Efendi, Moh.; Hanif Fahruddin, Ahmad (Akademika, 2024)
The aim of this research is to improve the ability to read the Al Qur'an of class 2A BK students at FKIP UNUGIRI using the Al Qur'an waqfi wal ibnot through the Tahsin learning method. The method used in this research uses the action research method (Action Research) using giving cycles and each cycle has four main activities. There are four main activities in each cycle, namely (1) planning, (2) action, (3) observation, and (4) reflection. In data analysis, researchers used a calculation of the percentage of learning completeness of at least 75% to 80%, based on the results of collaborators by looking at the results of initial observations, actions and final results of actions. The picture obtained by researchers during pre-research shows a figure of 30% for initial reading ability, so that when implementing the actions of researchers and collaborators it increases by 45% to 50%. This criterion is based on initial capabilities, availability/adequacy of infrastructure. The results of pre-research data analysis showed that the percentage of BK 2A students' reading ability was 29.87%, at the end of cycle I the percentage of reading ability was 49.81% and at the end of cycle II the reading ability was 76.88%.